2014
DOI: 10.1152/ajpregu.00064.2014
|View full text |Cite
|
Sign up to set email alerts
|

Physiological impacts of elevated carbon dioxide and ocean acidification on fish

Abstract: Most fish studied to date efficiently compensate for a hypercapnic acid-base disturbance; however, many recent studies examining the effects of ocean acidification on fish have documented impacts at CO2 levels predicted to occur before the end of this century. Notable impacts on neurosensory and behavioral endpoints, otolith growth, mitochondrial function, and metabolic rate demonstrate an unexpected sensitivity to current-day and near-future CO2 levels. Most explanations for these effects seem to center on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
377
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(390 citation statements)
references
References 240 publications
(467 reference statements)
12
377
1
Order By: Relevance
“…Behavioral effects may not manifest until the later larval stages, after the development of gills and acid−base regulation. The many negative effects of elevated pCO 2 on the sensory systems and behavior of tropical reef fish larvae has been attributed to the disruption of the GABA and GABA A neurotransmitter and receptors (Nilsson et al 2012, Hamilton et al 2014, Heuer & Grosell 2014. The resiliency of the VOR to elevated pCO 2 despite the role of GABA as the primary inhibitory neurotransmitter (Spencer & Baker 1992) suggests that white seabass larvae, and perhaps the larvae of other fish, may utilize Na Subtle changes in the VOR were discernible in our experiments.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Behavioral effects may not manifest until the later larval stages, after the development of gills and acid−base regulation. The many negative effects of elevated pCO 2 on the sensory systems and behavior of tropical reef fish larvae has been attributed to the disruption of the GABA and GABA A neurotransmitter and receptors (Nilsson et al 2012, Hamilton et al 2014, Heuer & Grosell 2014. The resiliency of the VOR to elevated pCO 2 despite the role of GABA as the primary inhibitory neurotransmitter (Spencer & Baker 1992) suggests that white seabass larvae, and perhaps the larvae of other fish, may utilize Na Subtle changes in the VOR were discernible in our experiments.…”
Section: Discussionmentioning
confidence: 56%
“…The effects of OA on marine fish are diverse (see review by Heuer & Grosell 2014), variable and most severe during the early life-history stages (Rombough 1988, Tseng et al 2013. The dynamics of these stages are critical in determining future population size and recruitment success (Houde 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have reported downregulation of VHA mRNA in gills from fish exposed to OA (e.g. Esbaugh et al, 2012;Tseng et al, 2013), which, as pointed out in a recent review (Heuer and Grosell, 2014), was most likely due to downregulation of branchial HCO 3 − secretion to seawater and H + reabsorption into the blood.…”
Section: A/b Regulationmentioning
confidence: 86%
“…This has also been referred to as a 'switch' in GABA A R action in other studies (see Tyzio et al, 2006). Nilsson et al (2012) sparked a flurry of studies in which gabazine was applied to a variety of animals that were exposed to elevated CO 2 and subjected to diverse tests ( gabazine reversed the effects of elevated CO 2 (reviewed in Heuer and Grosell, 2014;Nilsson and Lefevre, 2016). One of those studies using gabazine was our own ; working on the California splitnose rockfish (Sebastes diploproa), we found increased anxiety-like behaviour in fish exposed to ∼1100 µatm CO 2 ( pH 7.75) for 7 days and subjected to the light/dark preference test .…”
Section: Discovery Of Oa-induced Behavioural Alterationmentioning
confidence: 99%